2019
DOI: 10.3390/w11081530
|View full text |Cite
|
Sign up to set email alerts
|

Local Scour at Complex Bridge Piers in Close Proximity under Clear-Water and Live-Bed Flow Regime

Abstract: In this study, we investigated the characteristics of scour at complex bridge piers in close proximity. The experiments were performed under both clear-water and live-bed flow regimes. We compare our results with those for a single complex pier. Further, the performance of existing predictors is discussed. In this study, four typical pier arrangements were adopted, including side-by-side with aligned or 30 • skewed flow, staggered, and tandem. The results show that the skew angle for a side-by-side arrangement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…This leads us to the conclusion that in estimating scour depth, the component of flow area reduction should be considered in addition to local scour. Similarly, Yang et al [106] found that for complex bridge piers in close proximity, the upstream pier significantly affects scouring at the downstream pier in comparison to individual piers, reducing scour rate for clear-water conditions and increasing the bedform celerity for live-bed conditions.…”
Section: Element Formulaementioning
confidence: 92%
“…This leads us to the conclusion that in estimating scour depth, the component of flow area reduction should be considered in addition to local scour. Similarly, Yang et al [106] found that for complex bridge piers in close proximity, the upstream pier significantly affects scouring at the downstream pier in comparison to individual piers, reducing scour rate for clear-water conditions and increasing the bedform celerity for live-bed conditions.…”
Section: Element Formulaementioning
confidence: 92%
“…The best form of the piers, the smallest scouring around it, was the rhombus 30°, rhombus 60°, oblong and cylindrical, respectively. In another experiment, Yang et al (2019) studied typical piers in both common and skewed piers to the flow. They found that the skewed piers increased the scouring rate around the piers significantly.…”
Section: Skew Anglementioning
confidence: 99%
“…The seabed looks 'alive', referred to as 'lived bed scour' (Chiew, 1984;Yang et al, 2019). Here, the critical velocity of the current, i.e., the velocity causing the critical shear stress of seabed, should be considered in the scour experiments (Liu et al, 2018).…”
Section: Experiments Arrangement and Test Conditionsmentioning
confidence: 99%